Wakefield damping in a pair of X-band accelerators for linear colliders - Roger M. Jones; Christopher E. Adolphsen; Juwen W. Wang; Zenghai Li (Physical Review Special Topics. Accelerators and Beams, 2006)
We consider the means to damp the wakefield left behind ultrarelativistic charges. In particular, we focus on a pair of traveling wave accelerators operating at an X-band frequency of 11.424 GHz. In order to maximize the efficiency of acceleration, in the context of a linear collider, multiple bunches of charged particles are accelerated within a given pulse of the electromagnetic field. The wakefield left behind successive bunches, if left unchecked, can seriously disturb the progress of trailing bunches and can lead to an appreciable dilution in the emittance of the beam. We report on a method to minimize the influence of the wakefield on trailing bunches. This method entails detuning the characteristic mode frequencies which make up the electromagnetic field, damping the wakefield, and interleaving the frequencies of adjacent accelerating structures. Theoretical predictions of the wakefield and modes, based on a circuit model, are compared with experimental measurements of the wakefield conducted within the ASSET facility at SLAC. Very good agreement is obtained between theory and experiment and this allows us to have some confidence in designing the damping of wakefields in a future linear collider consisting of several thousand of these accelerating structures.